Light microscopy morphological characteristics of the sperm flagellum may be related to axonemal abnormalities. (24th February 2014) - Mitchell, V.; Sigala, J.; Ballot, C.; Jumeau, F.; Barbotin, A. L.; Duhamel, A.; Rives, N.; Rigot, J. M.; Escalier, D.; Peers, M. C.
Summary Although electron microscopy provides a detailed analysis of ultrastructural abnormalities, this technique is not available in all laboratories. We sought to determine whether certain characteristics of the flagellum as assessed by light microscopy were related to axonemal abnormalities. Forty‐one patients with an absence of outer dynein arms (type I), a lack of a central complex (type III) and an absence of peripheral doublets (type IV) were studied. Sperm morphology was scored according to David's modified classification. Flagella with an irregular thickness were classified as being of normal length, short or broken. There were correlations between missing outer dynein arms and abnormal, short or coiled flagellum. Type III patients showed the highest flagellar defects (a short (P = 0.0027) or an absent flagellum (P = 0.011)). Just over 68% of the irregular flagella were short in Type III patients, whereas this value was only 34.5% in type I and 26.4% in type IV (P = 0.002). There was a negative correlation between misassembly and spermatozoa of irregular flagella (r = −0.79; P = 0.019). It is concluded that light microscopy analysis of flagellum abnormalities may help provide a correct diagnosis, identify sperm abnormalities with fertility potentials and outcomes in assisted reproduction technologies and assess the genetic risk.